Genetic analysis reveals multiple parentage in captive reared eastern hellbender salamanders (Cryptobranchus alleganiensis). Issue 6 (24th August 2015) - Unger, Shem D.; Williams, Rod N.
Abstract : Information on the parentage of captive reared clutches is vital for conservation head‐starting programs. Molecular methods, such as genotyping individuals with hyper‐variable markers, can elucidate the genealogical contribution of captive‐reared, reintroduced individuals to native populations. In this study, we used 12 polymorphic microsatellite loci to infer parentage of a clutch of 18 eastern hellbenders collected from a single nest from Buffalo Creek, West Virginia, subsequently reared in captivity, and used for translocations in Indiana. Collectively, these markers successfully detected the presence of multiple parentage for this species of conservation concern presently used in captive management programs in zoos across many states. This study highlights the need for genetic analysis of captive reared clutches used in translocations to minimize the loss of genetic diversity and potential for genetic swamping at release sites. Zoo Biol. 34:535–537, 2015. © 2015 Wiley Periodicals, Inc.